Prototype of an Electric Vehicle Based on Bigo.Land - Mikhail V. Chugunov; Irina N. Polunina; Alexander Yu. Ovchinnikov (Инженерные технологии и системы, 2025)
Introduction. Modern electric vehicle industry is actively developing in many areas. Developing design and implementing a design decision for an electric vehicle are urgent tasks, including many specific interconnected research, design and technological problems. This article discusses a prototype electric vehicle, in which there is implemented a design decision based on combined control, which includes manual, remote and program control. Aim of the Study. The study is aimed at developing and implementing a design decision for an electric vehicle prototype with a combined control system in manual, remote (by radio) and unmanned mode that allows the pilot to easily and safely change the control mode. Materials and Methods. To solve the problem, there were used modern modeling and design methods based on an integrated approach involving the development of virtual (CAx)and full-scale models based on the Bigo.Land constructor and ArduPilot. Results. The result of the study is an integrated model of an electric vehicle prototype in general and, in particular, a full-scale model, CAx models, a control system providing combined remote, software and manual control. The components (full-scale and virtual) of the integrated object are connected by the same control system. Discussion and Conclusion. The developed integrated software and hardware model of an electric vehicle prototype, trajectory control system and the results of this model analysis provide the functional of a combined electric vehicle control system and can be used by designers and manufacturers of this type of machinery.